'Crying over spilt milk?' Effect of post‐consumption dissonance on coping behaviour for online purchases. (12th August 2021) - Mahapatra, Sabita; Mishra, Abhishek
Abstract: Compared to traditional purchases, the temporal gap between the purchase, the delivery and the consumption of products for online purchases is a challenge for e‐sellers. A mismatch of expectations and consumption experiences causes a stronger post‐consumption dissonance for online purchases, the outcomes of which, in the form of emotions and coping responses, are under‐researched. For this work, data were collected from 895 randomly selected respondents and the model was validated through structural equation modelling. The findings support that cognitive and affective components of post‐consumption dissonance have a positive influence on negative emotions, a combination of anger, regret, and guilt. Such emotions are found to trigger coping responses of mental disengagement and seeking social support, but not product return. Additionally, the evoked negative emotions are found to be lower for the elderly and female consumers. Finally, it is found that individuals with maximization focus seek social support more than those with satisficing focus for coping. The study provides a unique model connecting post‐consumption dissonance with coping responses and offers insights to e‐sellers about effective ways to manage such dissonance.